Low demand mitigation options for achieving Sustainable Development Goals: Role of reduced food waste and sustainable dietary choice. (1st October 2022) - Some, Shreya; Roy, Joyashree; Chatterjee, Joyee Shairee; Butt, M. Huzaifa
Abstract: Food waste reduction at consumer end and balanced, sustainable healthy dietary choices featuring less meat and less processed food have clear climate change mitigation benefits. This paper synthesises the existing body of literature (2015 to 2022) following systematic evidence search and screening using Scopus database and Google Scholar to explore the link of these two demand side mitigation options with the Sustainable Development Goals (SDGs). Assessment shows that these mitigation options not only have synergies with energy saving (SDG 7) goal but are intricately linked with awareness and educational programmes (SDG 4 and SDG 12) along with technological solutions/innovation (SDG 9), much broader innovative policy designs (SDG 16) going beyond market incentives, and involvement of multiple social actors (SDG 17). In aggregate, synergies with the SDGs outweigh trade-offs. Trade-offs can be addressed through policy measures, strategic information sharing, creating partnerships among social actors. Specific interventions related to these two demand-side mitigation options are categorised using ' Avoid', 'Shift' and 'Improve' framework. This framework helps in categorising interventions/policy measures leading to various levels of emission reduction: incremental reduction through 'Shift' and 'Improve' interventions and absolute reduction through 'Avoid' interventions. A total of 92 interventions are identified. We summarised the social actors involved in implementing these interventions for each of the ' Avoid', 'Shift' and 'Improve' categories and outlined the scope for future research. Highlights: 92 interventions in reducing food waste and changing dietary choices are identified. Interventions either help to 'Avoid', 'Shift' or 'Improve' in emissions. Interventions need to come from a wide variety of social actors to drive final behavioural change. Food related demand side mitigation options advance SDGs but also have some trade-offs. Food related demand side mitigation options have strong positive link with SDGs 4, 16 and 17.